Analysis of the Influence of the Work Environment and Work Discipline on Employee Performance at CV. Mitra Rajaya South Jakarta - I Gede Marendra; Retno Japanis Permatasari; Chotamul Fajri (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This research aims to determine the influence of leadership style and work discipline on employee performance at CV. Mitra Rajaya South Jakarta. The sample in the study was 50 respondents using quantitative methods. This research technique uses validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, simple linear regression, multiple linear regression, correlation coefficients, coefficients of determination, and hypothesis tests. The results obtained in this research on work environment variables have a significant influence, there are employee performance variables with a value of 0.000 < 0.05. Meanwhile, the work discipline variable has a significant effect on the employee performance variable with a value of 0.000 < 0.05. Meanwhile, simultaneously the leadership style variable and the work discipline variable have a significant effect on the employee performance variable with the calculated F value > F table or (34.310 > 3.20).